Continuous theta burst stimulation for drug-resistant epilepsy - Carrette, Sofie; Boon, Paul; Klooster, Debby; Van Dycke, Annelies; Carrette, Evelien; Miatton, Marijke; Raedt, Robrecht; Delbeke, Jean; Meurs, Alfred; Vonck, Kristl (Frontiers in Neuroscience, 2022)
Introduction Repetitive transcranial magnetic stimulation (rTMS) may have anti-epileptic effects, especially in patients with neocortical lesions. Initial clinical trials demonstrated that the duration of the seizure reducing effect is relatively short-lived. In the context of a chronic condition like epilepsy, thetaburst stimulation (TBS) may represent a potential solution in optimizing treatment practicality and durability as it was demonstrated to be associated with longer-lasting after-effects. TBS has been studied extensively in diverse neuropsychiatric conditions, but a therapeutic TBS protocol has not previously been applied in epilepsy patients. Materials and Methods We performed a prospective open-label pilot study of 4-day accelerated continuous TBS (cTBS) treatment in patients with neocortical drug-resistant epilepsy. A treatment session consisted of 5 cTBS trains, each comprising 600 pulses presented in 50Hz triplet bursts every 200ms, delivered at 10-minute intertrain-intervals, targeted over the epileptic focus using a neuronavigation-guided figure-of-8 coil. Safety and feasibility, and seizure frequency were assessed as primary and secondary endpoints respectively over a 4-week baseline period, a 1-week treatment period and a 7-week follow-up period, using adverse event logging, electro-encephalography, cognitive and psychological questionnaires and a seizure diary kept by the patients and/or caregivers. Results Seven subjects (4M:3F; median age 48, IQR 25) underwent the treatment protocol. Adverse events were reported in all subjects but were mild and transient. No clinical or electrographic seizures were evoked during or immediately following stimulation. No deterioration was found in cognition nor in psycho-emotional well-being following treatment. Treatment burden was acceptable, but seems to depend on clinical effect, duration of ongoing effect and stimulation site. Median weekly seizure frequency and ratio of seizure-free weeks did not change significantly in this small patient cohort. Conclusion We report the results of the first ever trial of cTBS as a treatment for neocortical DRE. A 4-day accelerated cTBS protocol over the EF appears safe and feasible. Although the design and sample size of this open-label pilot study is unfit to reliably identify a therapeutic effect, results encourage further exploration of cTBS as an anti-epileptic treatment and potential optimization compared to conventional rTMS in a dedicated randomized controlled trial. (clinicaltrials.gov: NCT02635633)